2022
DOI: 10.1111/cns.13886
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neuroprotection mediated by secretome of human mesenchymal stem cells against experimental stroke

Abstract: Aims:Regenerative medicine literature has demonstrated that the therapeutic potentials of mesenchymal stem cells (MSCs) in experimental stroke are attributed to secreted bioactive factors rather than to cell replacement. Here, we explored the effects of secretome or conditioned medium (CM) derived from human embryonic stem cell-derived MSCs (hESC-MSCs) on hippocampal neurogenesis, inflammation, and apoptosis in experimental stroke.Methods: Ischemic stroke was induced by right middle cerebral artery occlusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
(181 reference statements)
0
10
0
Order By: Relevance
“…Coronal sections were stained as previously described. 30 , 31 Briefly, following deparaffinizing and hydrating with xylene and descending graded ethanol, the sections were incubated in 0.1% cresyl Violet solution (Nissl Staining, Sigma‐Aldrich), for 6 min at 58°C. Subsequently, they were dehydrated using increasing concentrations of ethanol, cleared by xylene, and cover‐slipped.…”
Section: Methodsmentioning
confidence: 99%
“…Coronal sections were stained as previously described. 30 , 31 Briefly, following deparaffinizing and hydrating with xylene and descending graded ethanol, the sections were incubated in 0.1% cresyl Violet solution (Nissl Staining, Sigma‐Aldrich), for 6 min at 58°C. Subsequently, they were dehydrated using increasing concentrations of ethanol, cleared by xylene, and cover‐slipped.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, human embryonic stem cell‐derived and umbilical cord MSCs decrease IL‐6 mRNA in murine models of middle cerebral artery occlusion. This decrease in IL‐6 may be relevant to the increased neurogenesis, increased angiogenesis, and decreased apoptosis seen in these treated animals 36,37 . Given the role of IL‐6 in inflammation following stroke, it is understandable that blocking this cytokine prior to potential exacerbated inflammation offers therapeutic benefit.…”
Section: A Favorable End Of the Double‐edged Sword?mentioning
confidence: 98%
“…Neurotrophic components, such as GDNF, NGF, and BDNF, are endogenous macromolecules that primarily support nervous system cell development and growth 83,84 . Long‐term memory and synaptic plasticity are other areas in which they are involved.…”
Section: Mscs and Neurological Diseasesmentioning
confidence: 99%
“…In addition to its anti‐inflammatory properties, the primary source of functional recovery following the use of MSC is the transfer of neurotrophic factors into the brain, which in turn stimulates neurogenesis as well as neuroprotection. Molecular research has demonstrated the presence of NTFs such GDNF, NGF, and BDNF in exosomes generated from MSCs 84,88–90 …”
Section: Mscs and Neurological Diseasesmentioning
confidence: 99%